Long-term care in South Taiwan - A case study of a nursing home in Hualien - CHING-HSING LIN; SU-FANG WU; SSU-YU LIN (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to learn more about the state of long-term care for the elderly and disabled in Southern Taiwan. A nursing home in a rural area served as the study’s case study.Methodology: A qualitative approach was taken for the study’s research design. The elder care market is analyzed using SWOT to determine its strengths, weaknesses, opportunities, and threats.Findings: This research examined the elderly healthcare industry critically, highlighting opportunities and challenges, as well as potential solutions.Implications/Novelty: This research demonstrated that although elderly care management is a relatively new field of endeavor in Taiwan, it will soon constitute the bulk of the country’s healthcare industry. It’s essential for aging with grace and honor and for the efficiency of caregiving work to improve. The government should keep working to make long-term care services more available and of higher quality for the elderly with disabilities.